One-pion charm baryon transitions in a relativistic three-quark model; Physics Letters B; Vol. 44, iss. 1-4 - Ivanov M. A.; Kornerb J. G.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Rusetsky A. G. (1999, 1999)
Title screen